Investigation of single-strand conformational polymorphism of the TP53 gene in women with a family history of breast cancer - BURBANO, Rommel Mario Rodriguéz (2014)
Breast cancer in families with germ line mutations in the TP53 gene has been described in the medical literature. Mutation screening for susceptibility genes should allow effective prophylactic and preventive measures. Using single-strand conformational polymorphism, we screened for mutations in exons 5, 6, 7 and 8 of gene TP53 in the peripheral blood of 8 young non-affected members (17 to 36 years old) of families with a history of breast cancer. Studies of this type on young patients (mean age, 25 years) are very rare in the literature. The identification of these mutations would contribute to genetic counseling of members of families with predisposition to breast cancer. The results obtained did not show any polymorphism indicating mutation. In our sample, the familial tumorigenesis is probably related to other gene etiologies.